Finding the Productivity of Implementing IoT in Malawi and improve the usage of IoT devices to enhance nation Building: A survey - Shibi, Rimlon; Grace, Ezhil; Rashmi, Glory; Ponkumar, D. David Neels (Journal of Ubiquitous Computing and Communication Technologies, 2022)
The Internet of Things (IoT) is a contemporary technology in today’s world by grabbing the industries, home and, research consideration with a firm stride. According to the research, the average number of IoT devices per household will be 50 million in this era. The evolution of IoT will make the existing household devices to be hoary and now it’s a good time to create IoT devices to be affordable for daily use by the survivors across the world. This research is to find out the productivity of implementing IoT and to avoid disturbing existing network architecture and the software Define Network (SDN) in the underdeveloped country like Malawi and the usage of IoT devices in every household, offices and in agriculture to enhance the development of Country.
Keywords: IoT; household devices; Malawi; automation; smart agriculture